THE INFLUENCE OF PRODUCT DIFFERENTIATION STRATEGIES, DIGITAL MARKETING AND PRODUCT INNOVATION ON COMPETITIVE ADVANTAGE IN THE SDRA.WEAR MUSLIM FASHION BUSINESS - Sri Mega Wahyuni Arwin; Agus Syam; Valentino Aris; Asmayanti; Andika Isma (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2025)
The Muslim fashion industry in Indonesia continues to grow in line with the increasing demand for apparel that aligns with Islamic religious and cultural values. Competition in this market has intensified with many local brands offering attractive designs. To survive and excel in this competition, Muslim fashion businesses must implement product differentiation strategies, digital marketing, and product innovation. This study aims to (1) analyze the significant influence of product differentiation strategies on competitive advantage, (2) examine the significant influence of digital marketing on competitive advantage, and (3) analyze the significant influence of product innovation on competitive advantage. The research employs a quantitative method using multiple regression analysis to examine the collected data, with instruments including surveys or questionnaires. The population of this study consists of SDRA.WEAR customers who have made purchases and provided online reviews. The sample was selected using convenience sampling, targeting 60 respondents who were easily accessible and willing to participate. The results of this study indicate that (1) there is no significant positive influence of the product differentiation strategy on competitive advantage in the Muslim fashion business SDRA.WEAR, (2) digital marketing significantly and positively influences competitive advantage, and (3) product innovation also has a significant impact on competitive advantage in the Muslim fashion business SDRA.WEAR.